Compositional differences between near‐isogenic GM and conventional maize hybrids are associated with backcrossing practices in conventional breeding. Issue 2 (4th September 2014) - Venkatesh, Tyamagondlu V.; Cook, Kevin; Liu, Bing; Perez, Timothy; Willse, Alan; Tichich, Ryan; Feng, Ping; Harrigan, George G.
Summary Here, we show that differences between genetically modified (GM) and non‐GM comparators cannot be attributed unequivocally to the GM trait, but arise because of minor genomic differences in near‐isogenic lines. Specifically, this study contrasted the effect of three GM traits (drought tolerance, MON 87460; herbicide resistance, NK603; insect protection, MON 89034) on maize grain composition relative to the effects of residual genetic variation from backcrossing. Important features of the study included (i) marker‐assisted backcrossing to generate genetically similar inbred variants for each GM line, (ii) high‐resolution genotyping to evaluate the genetic similarity of GM lines to the corresponding recurrent parents and (iii) introgression of the different GM traits separately into a wide range of genetically distinct conventional inbred lines. The F1 hybrids of all lines were grown concurrently at three replicated field sites in the United States during the 2012 growing season, and harvested grain was subjected to compositional analysis. Proximates (protein, starch and oil), amino acids, fatty acids, tocopherols and minerals were measured. The number of statistically significant differences (α = 0.05), as well as magnitudes of difference, in mean levels of these components between corresponding GM variants was essentially identical to that between GM and non‐GM controls. The largest sources of compositional variation were the genetic background of the different conventional inbred lines (males and females) used to generate the maize hybrids and location. The lack of any compositional effect attributable to GM suggests the development of modern agricultural biotechnology has been accompanied by a lack of any safety or nutritional concerns.